2015
DOI: 10.4102/jef.v8i3.122
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding tax compliance: taxpayers' attitudes and beliefs

Abstract: In a society the tax climate is determined by the interaction between taxpayers and tax authorities. In a ‘service and client’ climate, taxpayers do not expect authorities to automatically suspect them of being tax evaders. Evidence suggests that recognising good tax behaviour with strategies of rewards has a positive effect on voluntary tax compliance. Principles derived from the cognitive evaluation theory predict that when feelings of competence are affirmed and this is accompanied by a sense of autonomy it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This 'softer' approach involves more efficient resources with minimal cost and improves taxpayer and tax authority cooperation (Murphy, 2008). Previous studies found that the imposition of accommodative elements will increase tax morale, eventually improving tax compliance behaviour levels (Feld and Frey, 2007;Bornman, 2014;Bornman and Stack, 2015a;Rillstone, 2015). Previous studies focused on the elements of the accommodative approach, which includes good treatment provided by tax authorities (Feld and Frey, 2007;Verboon and Van Dijke, 2007;Hartner et al, 2008;Murphy, 2008;Razilina et al ,2012;Farrar et al, 2017;Nivakan, 2020) as well as tax rewards (Togler, 2003;Feld et al, 2006;Bazart and Pickhardt, 2011;Bornman and Stack, 2015a;2015b;Brockmann et al, 2016;Carillo et al, 2016;Dwenger et al, 2016;Putra and Amrie Firmansyah, 2018;Wilks et al, 2019;Koessler 2019;Abdul Rashid et al,, 2021).…”
Section: Accommodative Approach and Tax Compliance Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…This 'softer' approach involves more efficient resources with minimal cost and improves taxpayer and tax authority cooperation (Murphy, 2008). Previous studies found that the imposition of accommodative elements will increase tax morale, eventually improving tax compliance behaviour levels (Feld and Frey, 2007;Bornman, 2014;Bornman and Stack, 2015a;Rillstone, 2015). Previous studies focused on the elements of the accommodative approach, which includes good treatment provided by tax authorities (Feld and Frey, 2007;Verboon and Van Dijke, 2007;Hartner et al, 2008;Murphy, 2008;Razilina et al ,2012;Farrar et al, 2017;Nivakan, 2020) as well as tax rewards (Togler, 2003;Feld et al, 2006;Bazart and Pickhardt, 2011;Bornman and Stack, 2015a;2015b;Brockmann et al, 2016;Carillo et al, 2016;Dwenger et al, 2016;Putra and Amrie Firmansyah, 2018;Wilks et al, 2019;Koessler 2019;Abdul Rashid et al,, 2021).…”
Section: Accommodative Approach and Tax Compliance Behaviourmentioning
confidence: 99%
“…Similarly, Wilks et al (2019) opined that tax rewards are an element that should be considered in designing a more cost-effective policy to maximise tax compliance behaviour. In addition, the recommendation is made since tax rewards are proven to increase tax morale resulting in a better tax compliance behaviour level (Togler, 2003;Feld et al, 2006;Bazart and Pickhardt, 2011;Bornman and Stack, 2015a;Brockmann et al, 2016;Carillo et al, 2016;Dwenger et al, 2016;Putra and Amrie Firmansyah, 2018;Wilks et al, 2019;Koessler, 2019).…”
Section: Accommodative Approach and Tax Compliance Behaviourmentioning
confidence: 99%
“…Because we focus on the rewarding part of the SIR methodology (see [1][2][3][4]), where the taxpayers deal with different kind of benefit-values in their systematic utility, risk aversion matters linked to the tax audit probability are not explicitly included in our model. The choice set has been selected to be only a specific finite discrete subset of all the potential (continuum) set of potential alternatives.…”
Section: This Contributionmentioning
confidence: 99%
“…The SIR score represents the degree of fiscal reliability recognized to each taxpayer and, if the SIR score is greater than or equal to a given threshold, the taxpayer can access a bonus scheme, which consists of some tax and economic benefits. This is a relevant recent theme and concerns the leverage tools a tax administration can use to influence the perceived utility of taxpayers, bringing them toward higher compliance levels: the rewarding of the compliant taxpayers, instead of the traditional methods of enforcement through audit and penalties for the non-compliant ones, emphasizes the use of the "carrot" for compliance rather than the "stick" for non-compliance (see, among others, [1][2][3][4][5]).…”
Section: Introductionmentioning
confidence: 99%
“…Despite raising a significant amount of revenues, there has been controversy as to whether governments should conduct tax amnesty programs. Contrary to recognizing good tax behavior with rewards (Bornman & Stack, 2015), tax amnesties may discourage lawabiding taxpayers who perceive law breakers being rewarded for non-compliance and they make current taxpayers believe that there will be future amnesties thereby reducing their incentive to be filing timely (Leonard & Zeckhauser, 1987). However, despite this possibility, several countries, even as far developed as the USA, have been conducting tax amnesties time and again.…”
mentioning
confidence: 99%